2017
DOI: 10.18203/2394-6040.ijcmph20172165
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of facilities and activities under integrated child development services in a city of Darjeeling district, West Bengal, India

Abstract: INTRODUCTIONICDS is recognized as unique community based outreach system for child nutrition and development programme. It is the most comprehensive scheme of India Government for early childhood. The programme was launched on 2 nd Oct 1975 in thirty three projects with aim of reducing malnourishment level and was targeted at children in age group 0 to 6 year and pregnant and lactating mother. During the 6 th five year plan it was included under the new 20 point programme and achieved the status of a national … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 2 publications
1
8
1
Order By: Relevance
“…In the study conducted in Darjeeling, 86.66% AWCs were found to be running in pucca buildings. 3 The AWC in the current study had adequate floor space, but in a study in Gujarat only 53.3% AWCs were found to have adequate indoor space. 4 This AWC had separate toilet facility, but in their study Saha et al found that toilet facility was absent in 43.33% AWCs.…”
Section: Discussioncontrasting
confidence: 61%
See 4 more Smart Citations
“…In the study conducted in Darjeeling, 86.66% AWCs were found to be running in pucca buildings. 3 The AWC in the current study had adequate floor space, but in a study in Gujarat only 53.3% AWCs were found to have adequate indoor space. 4 This AWC had separate toilet facility, but in their study Saha et al found that toilet facility was absent in 43.33% AWCs.…”
Section: Discussioncontrasting
confidence: 61%
“…In a study in Darjeeling by Saha et al, it was observed that 33.33% AWCs were running in rented Govt building and in a study conducted in Gujarat, 66.7% of buildings were owned by state. 3,4 In a study in Amritsar, it was found that only 24% of the AWCs had their own building. 5 In a study by Debata et al, out of 21 anganwadi centers, 81% were found to be functioning in government allotted buildings, 4.8% were functioning in a rented premise while remaining 14.2% were functioning in other non allotted government buildings like school or panchayat building.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations